Intermittent hypoxia-induced enhancement of sociability and working memory associates with CNTNAP2 upregulation - Zhang, Qing; Xu, Lu; Bai, Yang; Chen, Peiye; Xing, Mengen; Cai, Fang; Wu, Yili; Song, Weihong (Frontiers in Molecular Neuroscience, 2023)
Hypoxia is an environmental risk factor for many neurological disorders throughout life. Prenatal and perinatal hypoxia contributes to autism spectrum disorder (ASD), while hypoxic conditions in the elderly facilitate memory deficits. However, the effects of hypoxia on adolescence have not been addressed. In this study, we discovered that intermittent hypoxia treatment improved social behaviors and working memory in adolescent mice. CNTNAP2, a critical molecule in ASD pathogenesis, was increased in the brains of hypoxia-treated mice. To explore the molecular mechanism, we identified the transcription start site of the human CNTNAP2 gene and analyzed its transcriptional activation. Finally, we found that hypoxia upregulated CNTNAP2 by interacting with functional hypoxia response elements in CNTNAP2 promoter. Our study provides novel insights into intermittent hypoxia’s impact on development and the interaction between genetic and environmental risk factors in ASD pathogenesis.